The Effect of Learning Activity Using Talking Pen to Improve Student Learning Motivation - Ukhtul Iffah; Aisyatur Rodiyah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
Learning motivation was a studied manner from student and the first actor to certainly study result. Talking pen was learning for students to motivate them in sharing an opinion. The population of this research was all students of MTs. Nurul Jadid Mlandingan Situbondo, consisting of 58 students and the sample was using random sampling method by 10 students of VII- B and 15 students of VII-A. The instrument data collection used observation, interview, and test, the researcher analyzed normality test and homogeneity by (SPSS). From the test on mean VII A=0,76,00 more than 0,5. So in the research was normal, H1 was accepted and from VII B= 0,82,6 more than 0,5. So the research was normal, so H1 was accepted. For the homogeneity test where the test of pre-test was homogeneity, the significant was0,892. It means that the significance was more than 0,05, which H1 was accepted. Based on the test of post-test, the homogeneity significance was 0,136. It means that the significance was more than 0,05, so H1 was accepted. Based on the result of the t-test, the pre-test and post-test are significant. t-test must be under 0,05 and in the table are 0,000, So the effectiveness and H1 were accepted.